Pioglitazone for the treatment of type 2 diabetes in patients inadequately controlled on insulin - Schwartz S (Dove Medical Press, 2010)
Stanley S SchwartzDiabetes Disease Management at the University of Pennsylvania, Penn Presbyterian Medical Center, Philadelphia Heart Institute, Philadelphia, Pennsylvania, USAAbstract: Insulin resistance and impaired beta-cell function are primary defects that occur early in the course of development of type 2 diabetes. Insulin resistance leads to hyperinsulinemia in order to maintain normal glucose tolerance. In most cases of type 2 diabetes, beta-cell dysfunction develops subsequent to the development of insulin resistance, and it is not until such beta-cell dysfunction develops that any abnormality in glucose tolerance is seen. Insulin resistance is a primary defect in type 2 diabetes. The risk of coronary heart disease is significantly increased in patients with type 2 diabetes. Cardiovascular disease causes 80% of all diabetic mortality, and in 75% of those cases, it is a result of coronary atherosclerosis. These points provide a rationale for early and aggressive management of cardiovascular risk in patients with diabetes. Thiazolidinediones represent an effective tool for targeting some features of this increased risk as they decrease insulin resistance and can prevent and/or delay diabetes progression.Keywords: pioglitazone, type 2 diabetes, insulin